Garnering nature friendly agriculture practices: 1990 to 2020. When science simplification, participatory co production and generous sharing is valued - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Field tested practices, methodologies and approaches to regenerating agriculture and associated ecosystems are featured in this compilation . Mostly experiences from across Asia are included , the compilation is based on publications generated through participatory writeshops, organised over thirty years featuring a wide range of stakeholders, disciplines and donors. Participatory approaches in resource management and farmer-centered approaches are prominently featured . A wide range of ecosystems are featured, coastal, drylands, mountains and lowlands in the presentations of options and approaches. These are being presented because of their continued relevance to the current interest in regenerative agriculture, nature based solutions , ecosystems based adaptation and climate change.